2007
DOI: 10.1002/aic.11118
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline activated layered double hydroxides as solid acid‐base catalysts

Abstract: in Wiley InterScience (www.interscience.wiley.com).Activated layered double hydroxides (LDHs) with high crystallinity, obtained by calcination/rehydration of LDH precursors synthesized by urea decomposition, have higher catalytic activity in acetone self-condensation and Knoevenagel reactions than less crystalline materials obtained from LDH precursors synthesized by titration coprecipitation. The activated LDHs possess both basic and acidic sites. High resolution transmission electron microscopy (HRTEM) confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 44 publications
6
58
0
1
Order By: Relevance
“…3B), where the hexagonally lamellar morphology was integrally preserved after calcination at 500°C. It was interesting to note that the calcination process did not alter the morphology and the size of the LDO Mg/Al 4.0 particles, similar to the result reported by Lei et al [23]. This was in agreement with the assumption from IR that the LDO Mg/ Al 4.0 remained the hydrotalcite layered structure (Fig.…”
Section: Sem Imagessupporting
confidence: 90%
See 2 more Smart Citations
“…3B), where the hexagonally lamellar morphology was integrally preserved after calcination at 500°C. It was interesting to note that the calcination process did not alter the morphology and the size of the LDO Mg/Al 4.0 particles, similar to the result reported by Lei et al [23]. This was in agreement with the assumption from IR that the LDO Mg/ Al 4.0 remained the hydrotalcite layered structure (Fig.…”
Section: Sem Imagessupporting
confidence: 90%
“…Another reason for the enhanced activity in the LDO Mg/Al 4.0 might be that the precursor LDH Mg/Al 4.0 showed better crystallinity in the XRD and SEM data and the loss of the lamellar structure had previously been linked to poor activity [25]. The high crystallinity resulted in a regular arrangement of hydroxyl groups on the surface and a high density of appropriately acid-base balance [23]. The high catalytic activity and selectivity of the LDOs for the synthesis of PM were attributed to the presence of a high density of the medium basic sites.…”
Section: Catalytic Performancementioning
confidence: 93%
See 1 more Smart Citation
“…1 have exhibited extensive research interest in a number of areas, such as catalysis, [4][5][6] adsorption, 7,8 ion exchange, 4,9 and especially in drug delivery system as a novel biomaterials 1,[10][11][12] due to their low cost, ease of preparation, ion-exchange property, low cytotoxicity, and high biocompatibility. 1,13,14 Ambrogi et al 10 reported that the loosely flocculated ibuprofen (IBU)-intercalated Mg-Al-LDH nanoparticles (\200 nm) obtained by ion-exchange with chloride intercalated Mg-Al-LDH precursor showed almost 80% of IBU released only after 30 min ascribed to a dissolution mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…23 Thus, a large class of isostructural materials can be obtained by changing the metal cations, the molar ratio of M 2þ /M 3þ , or the interlayer anions. LDHs have a wide range of applications as catalysts or catalyst precursors, 24,25 microcontainer, and microreactor, 26,27 etc. Calcination of LDHs has been reported to be an alternative to the traditional chemical and physical methods for the fabrication of a wide variety of mixed metal oxide (MMO) nanocomposite materials composed of metal oxide and spinel phases, [28][29][30] and such various MMO materials displayed outstanding magnetic, 31,32 catalytic 28,33 and textual properties.…”
Section: Introductionmentioning
confidence: 99%